Upaya Kontribusi Melalui Keterlibatan Pengabdian Mahasiswa dalam Proses Pekerjaan Shotcrete Lereng Tunnel /Terowongan Samarinda - Pratiwi, Dheka Shara; Haekal, Muhammad; Agustina, Fitriyati; Asnan, Muhammad Noor; Pamungkas, Pulung Priyo (Lembaga Dongan Dosen, 2025)
This community service project engaged Civil Engineering students and faculty from Universitas Muhammadiyah Kalimantan Timur (UMKT), in collaboration with PT Ciriajasa CM, in a two-month partnership on the Samarinda Tunnel Project. The program provided students with a platform to integrate classroom theory with real-world practice, specifically focusing on the application of shotcrete methods for slope stabilization in challenging tunnel environments. Through a partnership with industry experts, students implemented high-pressure shotcrete techniques aimed at enhancing slope stability, supporting structural durability, and contributing to sustainable infrastructure development. Using a participatory observation approach, students conducted field observations, interviews, and theoretical-to-practical comparisons, culminating in a comprehensive analysis of shotcrete quality testing at UMKT’s laboratory. This project not only advanced students' technical skills but also highlighted the significance of academic-industry collaboration in merging theoretical knowledge with applied fieldwork for sustainable construction practices.